Investigating the effect of material and printing parameters on the mechanical properties of neat and modified LDH/ABS nanocomposites for FDM 3D printing - Labuschagne, F.J.W.J. (Frederick Johannes Willem Jacobus) (University of Pretoria, 2022)
Dissertation (MEng)--University of Pretoria, 2022.